Cadeia produtiva: conexões intersetoriais e complexidade estrutural da produção brasileira - Sales, Mariana Gomes de Oliveira (Universidade Federal de São Carlos, 2022)
The arrangements of the production structure are divided by the links between sectors that interconnect the set of production chains, and these structural changes impact on the transformations of economic development. Although the literature has essays on these impacts, the terminologies of the productive structure in terms of production chain have always been disconnected, making it necessary to understand this dynamic from the point of view that not only the size of sectorial links is relevant, but also the economic distance between sectors. Thus, an interpretation will be presented about the dynamics of transformations of these processes, seeking to discuss the importance of the production structure, identify the production chains and the main sectors that are part of them. In this context, the present work seeks to analyze the links of the Brazilian production chain structure through the input-output analysis, as well as its evolution for the years 2010-2018, through the methodology of indicators estimated from the IPM (input-output matrix): indicator of average propagation length (APL), indicator of structural complexity (EC) and the indicator of strength of intersectoral links, developed by Dietzenbacher, Romero and, Bosma (2005). The results indicated that the Brazilian economy has relevant production chains that start with the Natural Resource Intensive Industry and Agriculture sectors. During the years 2010-2018, the economy lost some longer intermediations in its chains, but managed to maintain its composition. The growth rate of Structural Complexity over the years remained minimal, with no relevant changes in structural changes in new linkages. It is concluded that its specialization continued to focus on production in the Natural Resource Intensive Industry and Agriculture sectors, with a positive advance in the Science-Based Industry sector, but little progress in its development over the years.
Productive chain: intersectoral connections and structural complexity of the Brazilian production
Keywords: Cadeias de produção; Complexidade estrutural; Economia brasileira; Comprimento médio de propagação – APL; Estrutura produtiva; Production chains; Structural complexity; Brazilian economy; Average length of propagation – APL; Production structure; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::CRESCIMENTO, FLUTUACOES E PLANEJAMENTO ECONOMICO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL